Cover crop monocultures and mixtures affect soil health indicators and crop yield in the southeast United States. Issue 5 (31st August 2022) - Decker, Hannah L.; Gamble, Audrey V.; Balkcom, Kipling S.; Johnson, Anna M.; Hull, Noah R.
Abstract: The southeastern United States has a long history of soil degradation due to intensive agriculture and climatic factors. Conservation management practices such as cover cropping aim to improve soil productivity and restore soil health. Our objectives were to evaluate the performance of cover crops and their short‐term effects on soil health indicators for two southeastern soil types. Cover crop experiments were conducted at the Wiregrass (WREC) and Tennessee Valley (TVREC) Research and Extension Centers in Alabama from 2017 to 2021. Cover crop treatments included winter fallow, monocultures, and two‐ and three‐way mixtures of cereal rye ( Secale cereale L.), crimson clover ( Trifolium incarnatum L.), and forage radish ( Raphanus sativus L.) preceding a cotton ( Gossypium hirsutum L.)–legume peanut [ Arachis hypogaea L.] or soybean [ Glycine max (L.) Merr.] cash crop rotation. At TVREC, aboveground biomass for both rye and clover were greater than radish. All cover crops, except the radish monoculture, increased soil organic carbon (SOC) 19–30% in the top 5 cm at TVREC compared with winter fallow. Similarly, some cover crop treatments increased permanganate oxidizable carbon (POXC) compared with the fallow control. However, this effect was not observed at WREC. Cover crops did not produce many meaningful aggregate stability differences at either location. Treatments containing rye or clover decreased soil strength. by 14–22% at TVREC after 4 yr of cover crop utilization. Short‐term cover crop use improved selected soil health indicators and reversed soil degradation at one location evaluated, but these benefits were dependent on soil type and cover crop selection. Core Ideas: Cover crop mixtures did not improve specific indicators of soil health more than monocultures. Radish monoculture did not improve soil health indicators compared with fallow. Rye and clover cover crops decreased compaction in a silt loam Ultisol after 4 yr. Cover crops increased soil C by 19‐30% in the top 5 cm of a silt loam Ultisol. Cover crops did not improve soil health indicators in a loamy sand Ultisol.